Perbaikan Desain Mesin Pencacah Daun Pelawan Untuk Meningkatkan Kemampuan Proses Pencacahan - Suhdi, Suhdi; Damayanti, Lutiya; Saparin, Saparin (Jurnal Inovasi Teknologi Terapan, 2024)
The Pelawan leaf chopper machine is an annual product of LPPM Universitas Brawijaya Malang and in collaboration with several universities, one of which is Bangka Belitung University which is focused on the Pelawan forest, Namang village, Central Bangka Regency. The chopping machine used has dimensions of 30 x 30 x 3 mm, and uses a 200-watt electric motor drive with a voltage of 220 V/150 Hz, with Rpm 2800 and 2 blades in the hopper. During the machine testing process, there were still deficiencies in the tool components which caused the results of the chopping to not be chopped properly. Therefore, it is necessary to identify existing problems and make design improvements to the pelawan leaf chopper machine to increase the capability of the chopping process. Identification was carried out on a pelawan leaf chopper machine in the Mechanical Engineering Laboratory at Bangka Belitung University. From the identification it is obtained; Firstly, the number of blades is 2, which causes the chopping process to not be optimal. Second, the distance between the hopper wall gaps is too wide, which affects the level of fineness of the chopped results. For this reason, design improvements were carried out to provide several alternative concepts (sketches) for the number of blades from various constructions on the machine. The alternatives given are 3 concept variants, the first is a 90° tilt propeller concept variant, the second is a 45° tilt screw layout concept variant and the third is a straight concept variant and a 90° tilt layout. In this research, variations of the concept following the assessment criteria and a distance between the blades of 45° enabled maximum results to be obtained.